Inovační prvky projektu EPR - Martinek, Miroslav (Vysoké učení technické v Brně. Fakulta strojního inženýrství, 2010)
Cílem práce je nalezení inovačních prvků projektu EPR. V první části se práce věnuje úvodu a vysvětlení tlakovodních reaktorů. Popisuje jednotlivé části, jejich různé typy a zapojení v celku. Druhá část se zabývá novinkami a úpravami v projektu EPR, jako je rozložení budov, reaktor, bezpečnost, atd. Třetí část obsahuje jednoduchý výpočet zvoleného zařízení.

The target of this work is to find innovative elements of EPR project. In the first part the paper deals with an introduction to the topic and explains water pressurized reactors. It describes the individual parts of the mechanism and their various types as well as their interconnection into a complete unit. The second part gives attention to innovations and modifications of EPR project in terms of location of buildings, reactor or safety requirements. The third part contains a simple calculation of a chosen mechanism.
Inovation components of EPR project
Keywords: EPR – european water pressurized reaktor; tlakovodní; kontejnment; aeroball; corium; EPR – european water pressurized reactor; water-pressurized; containment; aeroball; corium